Thermo-catalytic degradation of PE and UHMWPE over zeolites with different pore systems and textural properties - Silva,B. J. B. (2020)
Abstract The thermo-catalytic degradation of polyethylene (PE) and ultra-high molecular weight polyethylene (UHMWPE) was studied in the presence of zeolites (ZSM-5, ZSM-22, and ferrierite) with different pore systems and textural properties. The zeolites were physically mixed with polymers in the proportion of 30 wt% and submitted to thermogravimetric analysis at heating rates of 5, 10, 20, and 30 °C.min-1. The activation energy of the degradation process was determined using the Flynn-Wall-Ozawa method. The addition of zeolites to polymers has considerably reduced the temperature of degradation. ZSM-22 demonstrated greater efficiency in the degradation of PE because it has a smaller crystallite size, promoting a shorter diffusional path for the polymer fragments coming from the surface. Ferrierite showed a lower energy level in the degradation of UHMWPE, showing the need for synergy between the accessibility of the structure and acidity of the catalyst to promote the cracking of this polymer.